How to decide appropriate percutaneous coronary intervention (PCI) technique for managing heavy calcified coronary lesions: serial case-report - Caesario, Fahreza; Rohman, Mohammad Saifur (Universitas Brawijaya, 2024)
Background: Coronary artery calcification (CAC) is still challenging for interventional cardiologists. Their contribution to major adverse cardiac events occurs from the high risk of stent thrombosis or in-stent restenosis and target lesion revascularization. Optimal preparation, such as coronary plaque modification before stenting, is required to reduce the risk of periprocedural adverse events. This case presentation aimed to describe the appropriate management of heavy calcified coronary lesions.Case Presentation: Two cases of heavy calcified coronary lesions with different baselines as Acute Coronary Syndromes (ACS) and elective PCI were presented. In our ACS patients, the Primary PCI was done by coronary angioplasty without stenting because of the complexity of the heavily calcified lesion. A referral to tertiary health care was made for further PCI procedures using a combination of calcium-ablation and balloon-based techniques. A treatable complication occurred after the orbital atherectomy was performed with good results. The second case was an elective PCI patient with heavy calcified lesions findings from coronary angiography. The balloon-based technique was performed using non-compliant and scoring balloons without complication and showed good results.Conclusion: The challenging points in managing heavy calcified coronary lesions are procedure complexity and the higher stent failure rate. Many modifying coronary calcification algorithms using advanced modalities have been proposed, which could be used to select the appropriate technique as experienced and increase the success rate.